Prevention of recurrent urinary tract infections by intravesical administration of heparin: a pilot study - Tova Ablove; Manish Patankar; Songwon Seo (Therapeutic Advances in Urology, 2013)
Objective: To assess the effect of bladder instillations using heparin on the rate of urinary tract infections in women resistant to standard therapy. Patients and methods: The medical records of all women who received bladder instillations between May 2009 and January of 2010 at the University of Wisconsin urogynecology clinic were reviewed. Eighteen women (mean age 67 years) with a history of recurrent urinary tract infections received intravesical instillations (heparin 40,000 U, 2% lidocaine 8 ml, sodium bicarbonate 4 ml) once weekly for 6 weeks. Patients were considered resistant to standard therapy if their condition failed to respond to chronic suppression antibiotic therapy; they had chronic infections and for this reason could not be placed on chronic suppression; or they were not candidates for chronic suppression due to drug allergies. The number of urinary tract infections was monitored during treatment and for 6 months after therapy. The urinary tract infection rates were compared with the rates of urinary tract infection in the 6 months before treatment. Results: Seventy-eight percent of patients responded to therapy. Subjects were thought to have responded to therapy if there was a greater than 50% reduction in the rate of urinary tract infection. Other variables reviewed included evidence of chronic infection, hormonal status, glomerular filtration rate, age, body mass index, antibiotic allergies, diabetes, hypertension, and chronic antibiotic therapy during bladder instillations. None of these variables were found to be statistically significant. Conclusion: Bladder instillations decreased the rate of urinary tract infection in this pilot study; this effect persisted into the post-treatment period. More research is needed to confirm these preliminary findings.